397 Time Series and Correlation Network Analyses to Identify the Role of Maternal Microbiomes on Development of Piglet Gut Microbiome and Susceptibility to Neonatal Porcine Diarrhea. (10th April 2018) - Zhang, Z; Kwawukume, A; Moossavi, S; Sepehri, S; Nyachoti, M; Khafipour, E
Abstract: Neonatal porcine diarrhea (NPD) is the primary cause of pre-weaning mortality in the swine industry worldwide. However, the etiology and the risk factors that predisposes piglets to NPD are yet to be determined. Neonatal microbial colonization is a crucial step in gut development and maturation of the immune system to confer resistance against enteric pathogens. The transmission of the maternal microbiome plays a key role in neonates' initial gut microbiome establishment, suggesting piglets' maternal microbiome profile may potentially be associated with NPD. This study investigated the succession of neonatal piglets' gut microbiome and the association of the milk, vaginal and fecal microbiomes of sows with piglets' gut microbiome and diarrheic status. Milk, vaginal and fecal samples were collected from 27 sows before and after farrowing. Fecal samples also were collected from 5 piglets born to each sow on days 0, 1, 3, 5, 7, and 14 after birth. DNA was extracted from each sample and subjected to Illumina sequencing of V3–V4 regions of 16S rRNA gene and analyzed by QIIME2. Multivariate association with linear models (MaAsLin) was used to compare bacterial community composition between diarrheic and non-diarrheic piglets across time point. Correlation network analysis (CoNet) was used to explore microbial co-occurrence/mutual-exclusion relationships and identify hub operational taxonomic units (OTUs) that show the highest number of positive/negative correlations with other OTUs. Association between sow and piglet microbiomes were calculated by non-parametric Spearman's rank correlation analysis. The dominant successors in the piglets' guts were genera Escherichia (46%) and Clostridium (24%) during the first two days, rapidly supplanted by Bacteroides (20%) and Lactobacillus (18%) by days 5 to 7 which remained dominant until day 14. The richness of the sows' milk microbiota was positively correlated ( P < 0.05) with the richness of the piglets' fecal microbiota. Only sows' milk microbiome was significantly associated with the development of piglets' gut microbiome where maternal milk microbiome of diarrheic piglets had lower richness ( P = 0.05) than the non-diarrheic piglets. Our data suggests that the low diversity of milk microbiota could be a risk factor for NPD and can be potentially used as a biomarker to predict the risk of NPD in piglets.